A retrospective look on the role of trade and regional integration in Caribbean development - Bennett, Karl M. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1998)
Reviews the evolution of Caribbean thinking on the role of trade and regional integration in economic development.